2014
DOI: 10.1007/s11999-013-3040-5
|View full text |Cite
|
Sign up to set email alerts
|

Total Knee Arthroplasty After High Tibial Osteotomy: No Differences Between Medial and Lateral Osteotomy Approaches

Abstract: Background High tibial osteotomy (HTO) has long been accepted as an effective treatment for unicompartmental osteoarthritis of the knee in young, active adults. For varus knees, the two most commonly performed valgus-producing HTOs are the lateral closing wedge and the medial opening wedge. Regardless of technique, some HTOs fail and are converted to TKA. To our knowledge, no studies have directly compared TKAs done after lateral closingwedge osteotomies to those done after medial openingwedge osteotomies. Que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 10 publications
0
29
1
Order By: Relevance
“…However, the posterior tibial slope with long-term follow-up had no statistical difference between the OWO and CWO (95% CI: À1. 25…”
Section: Radiological Outcomesmentioning
confidence: 99%
“…However, the posterior tibial slope with long-term follow-up had no statistical difference between the OWO and CWO (95% CI: À1. 25…”
Section: Radiological Outcomesmentioning
confidence: 99%
“…However, a study from Preston et al (2014) showed no differences between lateral and medial osteotomy approaches regarding functional outcomes or survivorship of TKA.…”
Section: Discussionmentioning
confidence: 97%
“…Total knee arthroplasty after a closing-wedge is much more complicated and technically difficult than in an opening-wedge osteotomy. Preston et al 24 found that functional outcomes for arthroplasty after conversion from lateral closing-wedge HTO to be similar to those after conversion from medial opening-wedge HTO. The opening wedge, however, has the advantage of preserving the bone stock for future arthroplasty (Haslam et al 25 ).…”
Section: Table 3 Comparison Of Outcome Based On Implant Usedmentioning
confidence: 98%